The Analysis Of Organizational Structure Mapping At Cv Kolaborasi Pemuda - Oscar Satria (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research was conducted at a start-up company, CV Kolaborasi Pemuda Cerdas which has a complex organizational structure for a start-up company, namely the organizational structure for the business sector and also social community organizations. The purpose of this research is to find out how the company carries out human resource structure mapping, how the implementation of their organizational structure functions, and also how they overcome obstacles that occur in mapping their employees. This research uses qualitative methods by conducting interviews and observations to obtain research data. With this research, it is hoped that it can provide information and solutions to increase the effectiveness of the management of a company or organization in accordance with the work environment and employees.